PENGARUH PARTISIPASI ANGGARAN TERHADAP BUDGETARY SLACK DENGAN ASIMETRI INFORMASI, KETIDAKPASTIAN LINGKUNGAN,KOMITMEN ORGANISASI, DAN REWARD SEBAGAI VARIABEL MODERATING PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI PROVINSI RIAU - Putri, Sinta Tiara; Tanjung, Amries Roesli; Hasan, Mudrika alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of budgetary participation and information asymmetry, environmental uncertainty, organizational commitment and reward as moderating variable towards budgetary Slack at government institution in Riau Province. The population in this study are all government agencies in Riau Province, totaling 39 units. To determine sample is using purposive sampling method, the respondents of this study is the managerial planning, coordination, evaluation, supervision, staffing, negotiation and representation of each government institution inRiau Province. The number of samples to be taken from this population is as much as 78 respondents. Analysis of data using models Moderated Regression Analysis (MRA). The study states that the hypothesis testing results show that the budgetary participation and the budgetary participation moderated by organizational commitment has a significant influence on budgetary slack in the province of Riau. Budgetary participation moderated by budget asymmetry, budgetary participation moderated by environmental uncertainty, and the budgetary participation moderated by reward does not affect significantly to the budgetary slack in government institution of Riau Province.Keywords: Budgetary, Slack, Commitment, and Reward